Managing human resources in Africa - Kamoche, Ken N. (London ; New York : Routledge, 2004)
This volume addresses the shortage of knowledge about the nature, diversity and context of HRM in Africa and highlights the important trends and patterns that have been emerging on the continent.
Preface / Ken N. Kamoche, Gerry Nkombo Muuka, Frank M. Horwitz, Yaw A. Debrah -- HRM in South Africa / Frank M. Horwitz, Stella M. Nkomo, Mahamed Rajah -- HRM in Botswana / Dorothy Mpabanga -- HRM in Zambia / Gerry Nkombo Muuka, Kenneth Kaoma Mwenda -- HRM in Mauritius / Anita Ramgutty-Wong -- HRM in Tanzania / Yaw A. Debrah -- HRM in Kenya / Ken N. Kamoche, Stephen M. Nyambegera, Munyae M. Mulinge -- HRM in Ethiopia / Semaw Mekonnen, Aminu Mamman -- HRM in Ghana / Samuel Aryee -- HRM in Ivory Coast / Constant D. Beugre -- HRM in Tunisia / Mahmoud Yagoubi -- HRM in Libya / Abdoulhakem Almhdie, Stephen M. Nyambegera -- Conclusions: Toward a research agenda / Yaw A. Debrah, Frank M. Horwitz, Ken N. Kamoche and Gerry Nkombo Muuka.
Includes bibliographical references and indexes.
Print version record.
Keywords: Personnel management -- Africa; International business enterprises -- Personnel management; Personnel -- Direction -- Afrique; Entreprises multinationales -- Personnel -- Direction; BUSINESS & ECONOMICS -- Workplace Culture; BUSINESS & ECONOMICS -- Human Resources & Personnel Management; International business enterprises -- Personnel management; Personnel management; Africa